Muslim Subjectivities in Global Modernity : Islamic Traditions and the Construction of Modern Muslim Identities - Dietrich, Jung; Sinclair, Kirstine (International Studies in Religion and Society, 2020)
With critical reference to Eisenstadt's theory of "multiple modernities," Muslim Subjectivities in Global Modernity discusses the role of religion in the modern world. The case studies all provide examples illustrating the ambition to understand how Islamic traditions have contributed to the construction of practices and expressions of modern Muslim selfhoods. In doing so, they underpin Eisenstadt's argument that religious traditions can play a pivotal role in the construction of historically different interpretations of modernity. At the same time, however, they point to a void in Eisenstadt's approach that does not problematize the multiplicity of forms in which this role of religious traditions plays out historically. Consequently, the authors of the present volume focus on the multiple modernities within Islam, which Eisenstadt's theory hardly takes into account.